Targeting aerosol delivery to regions of nasal-associated lymphoid tissue (NALT) in three dimensional models of human intranasal airways using the BiVax intranasal atomizer - Laube, Beth L.; Kesavan, Jana; Farias, Gonçalo; Karavas, Nektaria; Blondel, Mathilde; Suman, Julie (Frontiers in Drug Delivery, 2024)
Well-organized nasal-associated lymphoid tissue (NALT) has been identified in the pharyngeal and tubal tonsils of both adults and children, and diffuse NALT has been identified in the superior, middle and inferior turbinate regions of children. However, it is not clear how to target these NALT sites with aerosolized vaccines. We explored whether head position and/or angle and distance of device insertion could be used to target fluorescein aerosol to NALT sites in three-dimensional printed models of the intranasal airways of an 18-and a 5-year-old (yo). Three head positions (upright [Up], tilted back 45° [45] and supine [Su]), two angles of insertion (30° and 45°) and two distances of insertion (6mm and 9mm) were tested. Fluorescein aerosol was generated by an Aptar Pharma BiVax 200 µL intranasal atomizer. Percent fluorescein deposition was quantified in the anterior nose, the upper horizontal third of the model (superior turbinate region), middle third (middle turbinate), lower third (inferior turbinate and nasopharynx combined) and exit filter. Mean percent deposition in both models was <0.5% in the upper third and on the exit filter for all test conditions. A multivariate analysis showed that deposition in either model was unaffected by the angles of insertion and distances of insertion. However, middle third deposition was significantly higher in the 5-yo than in the 18-yo (p=0.01) and anterior nose deposition was higher in the 18-yo than in the 5-yo (p<0.01). When data from both models were combined, middle third deposition was highest in the supine position with Up<4545>Su (p=0.03). These results suggest that, in individuals with similar nasal airway dimensions as our models: (1) supine and upright head positions might be used to target delivery of aerosolized vaccines generated by the BiVax intranasal atomizer to NALT sites in the middle turbinate and the inferior turbinate and nasopharynx combined, respectively; (2) delivery to the middle turbinate may be higher in children ≤5-yo; and (3) deposition in the anterior nose may be higher in adults, for all head positions. In vivo tests are needed to confirm these findings.